Physical attributes of Oxisols fertilized along five years with biosolids - de Melo, Valéria Peruca; Beutler, Amauri Nelson; de Souza, Zigomar Menezes; Centurion, José Frederico; de Melo, Wanderley José (Pesquisa Agropecuaria Brasileira, 2004)
The use of biosolids in agriculture has been the most viable alternative for domestic and industrial residues. The objective of this study was to evaluate the effect of biosolids addition on physical attributes of an Oxisol medium texture (LVd) and an Oxisol clayey (LVef). Accumulated doses of biosolids of 0.0, 25.0, 47.5, 50.0 Mg ha-1 were incorporated at 0.1 m depth. Deformed samples were collected in the fifth year after maize harvest, at the depths of 0.0–0.1, 0.1–0.2 and 0.2–0.3 m for the determination of granulometric composition and organic matter. Undeformed samples were collected with metallic cylinders of 0.03 m of height and 0.048 m diameter were taken for determination of bulk density, porosity and water retention in soil. The macroporosity increased at 47.5 Mg ha-1 and 50.0 Mg ha-1 of biosolids, in LVd and LVef, respectively, and the soil bulk density decreased at 50.0 Mg ha-1 in LVd, at the depth of 0.0–0.1 m. The application of 50.0 Mg ha-1 biosolids did not modify total porosity, microporosity and water retention in all tensions, in both soils. The effect of the application of biosolids depends on the soil type and de amount applied.